Oxidative Stress and Some Related Trace Elements in Women with Unexplained Infertility - Khansaa A. Hussien (Journal of Global Pharma Technology, 2018)
AbstractThis study aims to evaluate the oxidative stress and related trace elements (iron and copper) in women with unexplained infertility (UI). 60 women with unexplained infertility as well as (40) women with polycystic ovarian syndrome (PCOS) aged (20-35) year were included in this study. The women were divided according the type of infertility into primary and secondary groups (1ºUI, 2ºUI, 1ºPCO and2ºPCO) respectively. 50 healthy fertile women with the same age were included in this study as a control group. The results showed a significant increase in serum malondialdehyde (MDA) levels in all infertility groups compared to control group. Whereas serum levels of the antioxidants glutathione (GSH), superoxide dismutase (SOD) and ceruloplasmin (Cp) were significantly decreased in all infertility groups in comparison with control group. Serum levels of iron and copper significantly increase in unexplained infertility groups in comparison with explained infertility and control groups. No significant differences in iron levels between explained infertility groups and control. Whereas serum levels of the copper were significantly increased in explained infertility groups in comparison with control group. This study concluded that is a disturbance in serum oxidant- antioxidant balance in women with UI and PCOS infertility.Keywords: Unexplained infertility, Lipid per oxidation, Ceruloplasmin, Superoxide dismutase Iron, Copper.